2022
DOI: 10.1007/s11356-022-24261-5
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in surface water of Laguna de Bay: first documented evidence on the largest lake in the Philippines

Abstract: The pollution of aquatic systems by microplastics is a well-known environmental problem. However, limited studies have been conducted in freshwater systems, especially in the Philippines. Here, we determined for the first time the amount of microplastics in the Philippines’ largest freshwater lake, the Laguna de Bay. Ten (10) sampling stations on the lake’s surface water were sampled using a plankton net. Samples were extracted and analyzed using Fourier-transform infrared spectroscopy (FTIR). A total of 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Blue-colored microplastic was the most dominant color found in the study, which was consistent with the findings of Arcadio et al [ 60 ] in Laguna de Bay, Navarro et al [ 63 ] in Butuan Bay, and Sajorne et al [ 30 ] in Puerto Princesa, Palawan. Previous research revealed that blue-colored MPs were one of the colors highly associated with ropes, safeguard lines, and fishing materials [ 95 , 96 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Blue-colored microplastic was the most dominant color found in the study, which was consistent with the findings of Arcadio et al [ 60 ] in Laguna de Bay, Navarro et al [ 63 ] in Butuan Bay, and Sajorne et al [ 30 ] in Puerto Princesa, Palawan. Previous research revealed that blue-colored MPs were one of the colors highly associated with ropes, safeguard lines, and fishing materials [ 95 , 96 ].…”
Section: Discussionsupporting
confidence: 92%
“…In terms of shape, the Cagayan de Oro River, Philippines, was dominated by fiber MPs, similar to the study conducted along the Pearl River, China, which accounted for 94.4% of the total [ 89 ]. In addition, microplastic studies in the Philippines such as the study undertaken by Arcadio et al [ 60 ] in Laguna de Bay, Navarro et al [ 63 ] in Butuan Bay, and Sajorne et al [ 30 ] on Puerto Princesa Beach, Palawan were all dominated by fiber MPs. One of the causes of the release of fiber MP is washing a garment that can shed more than 1900 fibers per wash, releasing more than 100 fibers per liter of effluent [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was reported that 4,319,981 anthropogenic litter were collected from land, underwater, and watercraft cleanups last 2017, wherein mostly were plastic debris [15] which indicated that the Philippines was no exception from the presence of microplastics. The occurrence of microplastics from Majalar Bay [16], Molawin watershed in Laguna [17], Laguna de Bay [18], and from the surface water of five rivers connecting to Manila Bay namely: Cañas River; Meycauayan River; Parañaque River; Pasig River; and Tullahan River [19][20] was recently determined. Microplastics were also isolated in the aciddigested mussel soft tissue of Asian green mussels cultured in Bacoor Bay [9], in detritus-feeding mullets, and herbivorous rabbit fish in Eastern Visayas [21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on plastic pollution has been growing over the past decade, however there is limited data regarding marine plastic pollution in the Philippines. Studies carried out in the Philippines mostly focused on sediments and water (Arcadio et al, 2022;Navarro et al, 2022;Browne et al, 2011;Esquinas et al, 2020;Kalnasa et al, 2019;Paler et al, 2019) and living organisms (Argamino & Janairo, 2016;Abreo et al, 2016;Espiritu et al, 2019;Bucol et al, 2020). There are a few studies on sandy beaches (Sajorne et al, 2021), but none has focused on tourism as a contributing factor.…”
Section: Introductionmentioning
confidence: 99%